"Any Reason is Valid:" How an Unexpected Abortion Disclosure is Received by an Online Community. Issue 2 (17th February 2023) - Jones, Aubrey; Huslage, Melody; Dalton, Miranda
ABSTRACT: This study utilized a social media post by a well-known social media influencer and the accompanying 63 responses to explore feelings and experiences related to abortion. This study employed qualitative thematic analysis and identified three themes related to reasons for abortion (i.e., relationship issues, not being ready for pregnancy, and other reasons ) and one supplemental theme of bystander support . Findings highlight the efforts of many respondents to normalize abortion as an issue of women's health and women's rights. In fact, in response to the original post's discussion regarding valid reasons for an abortion, most respondents remarked similarly that any reason is valid. While study limitations include concerns regarding generalizability, this study provides access to abortion experiences outside of a traditional health clinic survey and insight into the abortion beliefs of women, both who have and have not experienced an abortion. Findings are in line with previous studies which found that multiple reasons are cited for obtaining an abortion, but also revealed a more supportive climate than the divisive discourse typically portrayed in the media. This suggests the timing may be conducive for efforts aiming to normalize abortion and reduce stigma, including potential avenues for interventions (e.g., social networks and platforms). Lastly, the innovative use of social media to inform this study should be considered by others as they seek to understand and explore topics that can be challenging to study.